Integrating ESG Pillars for Business Model Innovation in the Biopharmaceutical Industry - Annesha Bhattacharya; Sonali Bhattacharya (Australasian Accounting, Business and Finance Journal, 2023)
The study explores critical factors that impact the Business Model of Biopharmaceutical firms and assess how ESG pillars can aid in Business Model innovation. Semi-structured personal interviews were conducted in face to face meetings with experienced industry professionals from cross-functional domains to attain diverse insights. The objective was to explore the relevance of ESG factors and their interplay, during Business Model Innovation from the perspective of experts in the Biopharmaceutical industry. Analytical Hierarchy Process (AHP) – a structured approach is applied to understand the criticality of various factors in sustainable business models. The study revealed that special emphasis should be laid on the Business Model and Governance Pillar – for re-designing innovative and sustainable business models. Social and Environment factors, although important, were rated lower on priority as such issues are usually focused upon by organizations at a higher level of maturity, after the basic hygiene factors are met. Some of the factors which were prioritized for Business Model innovation are Patient Health and Safety, Ethical marketing and advertising, Waste/ Effluent Management, Employee Health, Safety and Wellness, Patient value propositions, Building strategic resources and competencies, Product Quality & Safety and Business ethics and competitive behavior. Integrated reporting is another value-added dimension that was stressed by the respondents, to have a seamless and transparent communication channel established with all stakeholders. Aligning business metrics with ESG metrics is the focal point of this study, and the impact of each pillar on Biopharma Business Models was evaluated by industry experts. Integration of ESG parameters for Business Model Innovation is the new mantra for forward looking companies, and this study would help frame strategies for the Biopharma industry for sustainable value creation. The impact created by Business Model Innovation at an industry level will help create value for the society at large (who are the key beneficiaries of Biopharma products and services), and such studies would help add to the knowledge base.
Keywords: Business Model Innovation; ESG Pillars; Biopharmaceutical Industry; Sustainability; Integrated reporting; Value based investing